Penerapan Media Mind Mapping Tipe Network Tree untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Sosial Madrasah Ibtidaiyah - Nursoviani, Listiana Damaya; Sahal, Yosep Farhan Dafik; Ambara, Bani (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2019)
This research is motivated by the low learning outcomes of grade 3 students at SDN 2 Cidolog on social studies subjects. This is by teaching social studies the teacher always uses conventional and monotonous learning media, while students are asked to memorize information that has been heard from their teacher. While social studies learning is required to develop students' thinking abilities, so students can become active can also solve a problem. In an effort to improve student learning outcomes, researchers used Mind Tree Mapping Network Tree Type. The method used is the Classroom Action Research Method (CAR) model of Kurt Lewin. Data collection techniques used were interviews, observation and tests. After conducting research, the authors conclude that: Student learning outcomes in social studies have increased as in the first cycle that is obtained an average value of 72.7 students with 9 complete criteria and 9 incomplete as many people. Cycle II, the average value of students was 83.6 with 13 students completing criteria and 5 students who were unfinished and Cycle III, 91.3 students with an average criterion of 17 students and 1 student who were incomplete